Development and Preliminary Validation of the Salzburg Emotional Eating Scale - Meule, Adrian; Reichenberger, Julia; Blechert, Jens (Frontiers in Psychology, 2018)
Existing self-report questionnaires for the assessment of emotional eating do not differentiate between specific types of emotions and between increased or decreased food intake in response to these emotions. Therefore, we developed a new measure of emotional eating—the Salzburg Emotional Eating Scale (SEES)—for which higher scores indicate eating more than usual in response to emotions and lower scores indicate eating less than usual in response to emotions. In study 1, a pool of items describing 40 emotional states was used. Factor analysis yielded four factors, which represented both positive (happiness subscale) and negative emotions (sadness, anger, and anxiety subscales). Subsequently, the scale was reduced to 20 items (5 items for each subscale) and its four-factor structure was replicated in studies 2 and 3. In all three studies, internal consistencies of each subscale were  > .70 and mean subscale scores significantly differed from each other such that individuals reported the strongest tendency to eat more than usual when being sad and the strongest tendency to eat less than usual when being anxious (sadness > happiness > anger > anxiety). Higher scores on the happiness subscale related to lower scores on the negative emotions subscales, lower body mass index (BMI), and lower eating pathology. In contrast, higher scores on the negative emotions subscales related to lower scores on the happiness subscale, higher BMI, and higher eating pathology. The SEES represents a useful measure for the investigation of emotional eating by increasing both specificity (differentiation between specific emotional states) and breadth (differentiation between increase and decrease of food intake) in the assessment of the emotion–eating relationship.